Iraq Crude Oil Exports April, May, June 2016 and crude oil production rates, Gas Production Activities, Types of Oils and Asphalt - SOMO, Ministry of Oil / Oil Marketing Company (Journal of Petroleum Research and Studies, 2017)
Table (1) Iraq Crude Oil Exports April 2016 Table (2) Iraq Crude Oil Export- May /2106 Table (3) Iraq Crude Oil Exports June 2016 Table (4) crude oil production rates and crude discharge for April / 2016 Table (5) Oil Production Rates for April /2016 Table (6) crude oil production rates and crude discharge for May / 2016 Table (7) Oil Production Rates for May /2016 Table (8) crude oil production rates and crude discharge for June / 2016 Table (9) Oil Production Rates for June /2016 Table (10) Gas Production Activities, Types of Oils and Asphalt for April / 2016 Table (11) Gas Production Activities, Types of Oils and Asphalt for May / 2016 Table (12) Gas Production Activities, Types of Oils and Asphalt for June / 2016